Upaya peningkatan kinerja guru melalui teknik lesson study secara kolaboratif dan rutin di PAUD Terpadu Mustika Angkasa Kota Banjarbaru - Endang Sri Wardiyah (JPPTK: Jurnal Pendidikan Pembelajaran & Penelitian Tindakan, 2022)
Researchers use Lesson Study techniques which are carried out collaboratively and routinely in order to find out the increase in teacher awareness and responsibility for the main tasks and functions imposed by parents, society and government, to know the improvement of teachers in compiling and evaluating plans in carrying out teaching tasks so that the quality of learning improving, knowing the increase in teachers' understanding of their duties as learning agents, and forming and creating work discipline and a school work culture climate to improve the quality of learning. This research is school action research which consists of two cycles. The research procedure includes planning, implementation, observation, and reflection. The subjects in this study were teachers at PAUD Terpadu Mustika Angkasa with a total of 2 teachers. The results showed an increase in teacher performance. Judging from the results of the first cycle with an average value of 26.5 and in the second cycle it increased with an average value of 33. Thus, research through collaborative and routine Lesson Study techniques can improve the performance of teachers at PAUD Terpadu Mustika Angkasa.